QT dispersion in irritable bowel syndrome - Varim, Perihan; Karacaer, Cengiz; Varim, Ceyhun; Yaylaci, Selcuk; Vatan, Mehmet Bulent (International Journal of Research in Medical Sciences, 2019)
Background: The pathogenesis of irritable bowel syndrome (IBS) has not been fully elucidated. The gastrointestinal tract have a well-differentiated intrinsic nervous system and also this system is connected with nervous system. The symptoms of IBS are related with autonomic nervous system (ANS). It was also possible to see cardiovascular symptoms due to this link. This link can influence QT dispersion (QTd). The aim of this case control study is to show the cardiac effects of IBS by changes in QTd. Methods: There were 56 newly diagnosed patients with IBS and 60 control subjects were included in this study. IBS was diagnosed using the new Roma IV Criterias. Standard 12-lead electrocardiogram (ECG) were taken in both two groups. QTd and corrected QTd (QTcd), QT max, QT min, QT avarage, Corrected QT (QTc) min, QTc max, QTc avarage values were calculated with Bazzet Formula from rest ECGs. Results: There were 56 newly diagnosed patients with IBS and 60 control subjects were included in the study (p:0.94). The mean age of the patients and control patients were 51.75±10.41 years and 48.41±9.72 (p: 0.53) years, respectively. QTd and corrected QTd (QTcd), QT max, QT min, QT mean, Corrected QT (QTc) min, QTc max, QTc mean values were calculated. QTd and QTcd values were found to be significantly higher in the patients with IBS (40.2±7.18; 34.1±6.18 / 52±9.8; 50.6±7.61 Msec, respectively). It is concluded that, QTd (p: 0.022) and QTcd (p: 0.032) were significantly incresased in the IBS. Conclusions: Activation of ANS in the patients with IBS can affect QT period in ECG.